A Systematic Literature Review: Heat Flux and Its Relation to Sea Surface Temperature Variability - Samiaji, Budi Isman; Nuryadi, Ari (Universitas Negeri Padang, 2024)
Heat flow patterns or heat flux play an important role in sea surface temperature (SST) variability and this is very important for understanding the dynamics of climate and marine ecosystems. Heat flow between the atmosphere and ocean can influence ocean circulation patterns, climate variability, and phenomena such as marine heat waves. The aim of this paper is to find out how heat flow patterns or heat flux influence sea surface temperature variability, marine ecology and extreme weather. Using a literature review methodology. It is hoped that from reviewing journals we can find out how heat flows influence sea surface temperature variability and marine ecology and extreme weather. Heat flow between the atmosphere and the ocean has a significant influence on sea surface temperature variability, especially in regions such as the Indian Ocean. Marine heat waves and changes in ocean heat content are clear examples of how heat flows can significantly influence sea surface temperatures. In addition, the influence of long-term heat flow patterns can influence the distribution of species in the sea